2011
DOI: 10.1071/rd10317
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the pregnancy-induced rise in cortisol concentrations in the ewe impairs the fetal insulin-like growth factor axis

Abstract: Maternal cortisol levels increase during pregnancy. Although this change is important for optimal fetal growth, the mechanisms of the changes in growth remain unclear. We examined whether alterations in maternal plasma cortisol concentrations are associated with changes in the fetal insulin-like growth factor (IGF) axis. Pregnant ewes in late gestation (115 ± 0.4 days) were studied: six control animals, five ewes given 1 mg/kg/day cortisol (high cortisol), and five adrenalectomized ewes given 0.5-0.6 mg cortis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
(80 reference statements)
0
3
1
Order By: Relevance
“…Similarly, in our studies, we have not found a decrease in fetal weight, although this may be a type II error resulting from low numbers of animals. However, as our laboratory did not find any change in concentrations of IGFs, nor changes in IGF expression in the heart in previous studies (27,47), the wellcharacterized effect of high-dose cortisol on growth appears not to be critical in the mechanism of cardiac dysfunction.…”
Section: Discussioncontrasting
confidence: 48%
“…Similarly, in our studies, we have not found a decrease in fetal weight, although this may be a type II error resulting from low numbers of animals. However, as our laboratory did not find any change in concentrations of IGFs, nor changes in IGF expression in the heart in previous studies (27,47), the wellcharacterized effect of high-dose cortisol on growth appears not to be critical in the mechanism of cardiac dysfunction.…”
Section: Discussioncontrasting
confidence: 48%
“…Maternal HPA axis activity and both maternal and foetal cortisol levels rise throughout pregnancy, reaching their zenith during birth ( 117 119 ). This rise plays an essential role in the terminal development of foetal lungs and initiating pulmonary surfactant production ( 120 ), as well as controlling hepatic ( 121 ), cardiac ( 122 ), cardiovascular ( 123 ), and G-I tract ( 124 ) maturation, as a coordinated series of events preparing the foetus for the transition to extra-uterine life.…”
Section: Immediate and Long-term Effects Of Oxytocin During Labour Bi...mentioning
confidence: 99%
“…Furthermore, they report that viral markers for SARS-CoV-2 were abundant in the hypothalamus of a 63-year-old male patient who died of COVID, but absent from the hypothalamus of controls (Nampoothiri et al, 2020). Very little work has been done on the possible neurodevelopmental consequences of low cortisol levels during pregnancy, but pregnancy is typically accompanied by substantial increases in cortisol (Mastorakos and Ilias, 2003;Jensen et al, 2011;Guardino et al, 2016). Several studies, conducted in sheep, indicate that lowering maternal cortisol during pregnancy alters placental morphology and reduces placental and uterine blood flow, which could result in restricted fetal growth (Jensen et al, 2005(Jensen et al, , 2007 and altered neurodevelopment, as previously discussed.…”
Section: Maternal Infection and Fetal Hypothalamic-pituitary-adrenal ...mentioning
confidence: 99%